Khitanan Massal dan Pemeriksaan Kesehatan dalam Rangka memperingati Hari Ibu Tahun 2024 di Gedung Sekretariat Bersama Pengurus Cabang Nahdatul Ulama Kabupaten Tabanan Bali - Gampur, Imelda Rismayani; Wisaradah, Putu Jalanidipuja; Sulastina, Elisabet; Zakiah, Siti (STIKES Advaita Medika Tabanan, 2025)
Social services such as mass circumcisions and health checks on the occasion of Mother's Day in 2024 are carried out to help people in need. Circumcision is an effort to improve reproductive health for men from an Islamic perspective. Apart from that, health checks can improve the level of public health. Objective: To mass circumcise boys who have not yet attained puberty and to detect early public health problems around the Secretariat Building with PC Nahdatul Ulama Tabanan. Method: This community service is a collaboration between LAZISNU Tabanan, YKM NU Tabanan and Stikes Advaita Tabanan. Mass circumcision was carried out using the electrocautery circumcision technique by the medical team, health examinations and counseling on post-circumcision wound care and nutritional education were carried out by the YKM NU Tabanan team and Advaita Tabanan stickers. Results: Mass circumcisions were carried out on 40 children, the circumcisions went well and no complications occurred to the participants during the circumcisions. Health check activities include blood pressure checks, weight checks, blood sugar checks, uric acid blood checks, cholesterol blood checks and nutritional education for the community around the secretariat building with PC NU Tabanan, participants were mostly women (61.1%), age 56-65 years old (72.2%) who have hypertension (72.2%) obesity (47.2%) GDS > 140 mg/dl (77.8 %) uric acid > 6 mg/dl (5.56%) cholesterol (19.4%). By carrying out this Community Service activity, it is hoped that the community will be able to continue routine health check-ups every month, carried out at existing health services. so that this will help to overcome all the health problems that the community has. Keywords: Mass circumcisions, health checks, Mother's Day